The effect of the fraud hexagon on Financial statement fraud in the finance sector companies Listed on the indonesian stock exchange from 2020 -2023 - Bertha Elvy Napitupulu; Muhammad Diva; Oktavia Marpaung; Frisca L. Siagian; Rudy Hedianton Saragih; Luky Yunia Wennadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Financial statements are documents that present a company’s financial information and serve as the basis for evaluating the company’s performance and financial stability. Financial statements contain information regarding the company’s management performance and reflect the company’s condition over a given business period. Every company strives to produce financial statements that are accurate, relevant, and reliable so as to demonstrate that its operations are running smoothly. Fraud is committed to manipulate financial statements so that they appear sound, relevant, and reliable. Financial statement fraud can be caused by various factors. Theories regarding the causes of financial statement fraud have evolved from the fraud triangle, fraud diamond, fraud pentagon, and fraud hexagon, where the factors are pressure, opportunity, rationalization, capability, arrogance, and collusion. This study aims to analyze the influence of the fraud hexagon—comprising pressure, opportunity, rationalization, capability, arrogance, and collusion—on financial statement fraud in financing sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The results of the study indicate that none of the factors in the fraud hexagon had an effect on financial statement fraud at financing sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period.